Evaluation of Spleen Function in Renal Transplant Patients and Controls by Liver-Spleen Scanning Using Qualitative and Quantitative Methods - Araújo MD, PhD, Nordeval Cavalcante; Orlando MD, PhD, Margarida Maria Camões; das Neves MD, Moises Bonifácio; de Souza MS, Raphael Sancho Sisley; Mandarim-de-Lacerda MD, PhD, Carlos Alberto (International Journal of Innovative Research in Medical Science, 2022)
Objective: The purpose of this study was to compare renal transplant recipients healthy controls, in order to find scintigraphic signs of hyposplenism or hypersplenism by using qualitative and quantitative liver-spleen scan parameters. Material and Methods: Scanning parameters were evaluated in 88 renal transplant recipients and 59 controls after administration of 5-mCi of 99mTc-stannous colloid. Spleen uptake was characterized as normal, low, or high in comparison to the liver and bone marrow pattern uptake was described as normal or high. The images were drawn over the liver and spleen for counting scintillations and measuring the area. Spleen/liver ratio from controls was correlated with qualitative spleen uptake of renal transplant recipients. Immunosuppressive regimens consisted of combinations of azathioprine or mycophenolate mofetil and rapamycin, tacrolimus or cyclosporine. Results: renal transplant recipients took up more radiocolloid and had larger livers and spleens than controls. Cases of lower (hyposplenism) and higher (hypersplenism) uptake in the spleen were more frequent in renal transplant recipients than in controls. There was a good correlation between spleen uptake of renal transplant recipients and spleen/liver ratio of controls. Discussion: renal transplant recipients liver and spleen took up more radiocolloid consistent with their enlarged state, likely due to activation of the mononuclear phagocyte system, probably by repeated exposure to infection. Low and high splenic uptake were found in renal transplant recipients, these findings are consistent with diagnosis of hyposplenism and hypersplenism respectively. Quantitative methods validated visual assessment.